Factors Associated with the Stunting in Toddlers in the Work Area of Tikson Raya Public Health Center - Fadjriah, Rasyika Nurul; Rusdianto, Rusdianto; Herman, Herman; Vidyanto, Vidyanto (Open Access Macedonian Journal of Medical Sciences, 2021)
Background: Stunting often called stunted or short, is a condition of failure to thrive due to chronic malnutrition and psychosocial stimulation and exposure to repeated infections in the First 1000 Days of Life (from fetus to child aged 2 years). Objective: The purpose of this study was to determine the factors associated with the incidence of stunting in the working area of the Tikson Raya Public Health Center, Banggai Laut District. The quantitative study with a case-control research design was applied. The number of samples used was 90 people with the Stratified Random Sampling technique. The data was collected by a questionnaire and analyzed by using univariate, bivariate, and multivariate analysis. Results: An association between breastfeeding (p=0.009), the timing of complementary feeding (p=0.009), history of infectious disease (p=0.001), basic health practices (p=0.000), environmental sanitation hygiene (p=0.000), knowledge of maternal nutrition (p = 0.000) with the incidence of stunting in the working area of the Tikson Raya Public Health Center, Banggai Laut District. The environmental sanitation hygiene variable was identified as the most related to the value of OR = 17.367. Conclusion: Exclusive breastfeeding, complementary breastfeeding, infectious diseases, basic health practices, environmental sanitation, and knowledge of maternal nutrition are associated with the incidence of stunting in toddlers in the working area of Tikson Raya Public Health Center, Banggai Laut District.